Inventory of Epiphytic Moss in the Tree Trunk Zonation of Jumog Waterfall Ngargoyoso Tawangmangu Karanganyar Central Java, Indonesia - Roziaty, Efry; Agustina, Putri; Rohmah, Siti Naily (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2019)
The concept of epiphytic plants is a critical plant that determines the processes that occur in ecosystems. Epiphytic plants especially Bryophytes or commonly moss is one of primary productivity. This study aims to record any epiphytic moss in their natural habitat in the Jumog Waterfall Forest Ngargoyoso in Karanganyar Tawangmangu Central Java. The method used in this study was purposive sampling, this method using exploration techniques. Field data observed were epiphytic plants from the Bryophyte groups (moss plants). The results showed that there were five moss colonies namely Bryum billardieri, Octoblepharum albidum, Leucobryum aduncum, Heteroscyphus coalitus and Pogonatum neesii, in 3 different zones of phorophytes, name zone I, II and III.